Report on business attachment with Heimann optoelectronics Singapore Pte Ltd. - Tan, Gek Hoon. (2009)
This report is to highlight the various responsibilites performed and experiences gained during the lO-weeks business attachment. Being attached to the HR department, I was able to put into practice what I have learnt. I have assisted in conducting interviews for the Production Operators and Engineering Assistants, which prove to be a very meaningful experience for me. I was exposed to the actual running of the department, the activities and functions held. However, I also realised the difficulties and problems faced in the actual functioning of the Department. Thus, all these had provided me with a clearer picture of Human Resource.